A study of the agglutination method in the diagnosis of glanders - Hayes, Fred M.; Smith, Martin G. (My University, 1908)
Introduction: Glanders is one of the most important infectious diseases of horses, asses and mules, and when transmitted to man one of the most fatal diseases of the human species. It runs an acute or chronic course attacking the lymphatic system, more especially in the upper air passages, lungs and skin.
Citation: Hayes, Fred M. and Smith, Martin G. A study of the agglutination method in the diagnosis of glanders. Senior thesis, Kansas State Agricultural College, 1908.
Keywords: Anatomy; Agglutination; Glanders Disease; Graduating theses; Senior theses; Theses